Zapotrzebowanie na controllera w trójmiejskich przedsiębiorstwach - wyniki badań empirycznych - Kotowska, Beata (Demand for Controller in Enterprises of Gdansk Urban Agglomeration - Results of Empirical Research, 2007)
The goal of the essay is the approximation of controller position on the grounds of employers expectations. The author conducted the examination of offers for controller position in the periods of 1996-1997 and 2005-2006. Basing on the results it was indicated what kind of changes occurred in the position designation, qualification requirements and scope of duties required from a controller.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 302-309